2021
DOI: 10.1016/j.jajs.2021.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Attune total knee arthroplasty: is there evidence of early tibial component de-bonding? A prospective cohort study with a minimum two year follow-up

Abstract: This is a repository copy of Attune total knee arthroplasty: is there evidence of early tibial component de-bonding? A prospective cohort study with a minimum two year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 30 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…The results are summarized in Table III. Five studies with a control group showed higher rates of RLLs, predominantly tibial or overall, for the ATTUNE groups, 20,23,24,29,27 with two demonstrating a significant difference. 24,29 Two studies reported no RLLs for the ATTUNE group in either the tibia or femur at a mean follow-up of about two years.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The results are summarized in Table III. Five studies with a control group showed higher rates of RLLs, predominantly tibial or overall, for the ATTUNE groups, 20,23,24,29,27 with two demonstrating a significant difference. 24,29 Two studies reported no RLLs for the ATTUNE group in either the tibia or femur at a mean follow-up of about two years.…”
Section: Resultsmentioning
confidence: 98%
“…26,31 Three studies reported on the progression of RLLs, 23,24,27 with two showing no progression. 23,27 One reported that medial tibial RLLs were progressive, with the rate increasing from 17% for the ATTUNE group at two weeks’ to 42% at two years’ follow-up. 24 One study compared patients in the ATTUNE group with RLLs with those without RLLs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations